2019
DOI: 10.1088/1361-6560/ab25ce
|View full text |Cite
|
Sign up to set email alerts
|

Range verification of radioactive ion beams of 11C and 15O using in-beam PET imaging

Abstract: In advanced ion therapy, the visualization of the range of incident ions in a patient's body is important for exploiting the advantages of this type of therapy. It is ideal to use radioactive ion beams for in-beam positron emission tomography (PET) imaging in particle therapy due to the high quality of PET images caused by the high signal-to-noise ratio. We have shown the feasibility of this idea through an in-beam PET study for 11 C and 15 O ion beams using the dedicated OpenPET system. In this work, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…S6 and S7. ion therapy 32 . Additionally, in a recent multi-institutional clinical study, carbon ion therapy showed favorable outcomes with limited toxicities for PC treatment 33 .…”
Section: Discussionmentioning
confidence: 99%
“…S6 and S7. ion therapy 32 . Additionally, in a recent multi-institutional clinical study, carbon ion therapy showed favorable outcomes with limited toxicities for PC treatment 33 .…”
Section: Discussionmentioning
confidence: 99%
“…An additional problem in the in-flight technique is the large momentum spread. This spread causes a shift between the Bragg peak and activity peak for RIB [83]. Even if this shift is smaller than the one observed using stable ions for treatment and projectile fragments for PET imaging (Figure 2), it increases with the momentum acceptance.…”
Section: Rib Productionmentioning
confidence: 83%
“…Because of the wide-open space and mobility, the system can be used to study the washout effect using animals [50][51][52][53][54]. It has been suggested that radioactive ion beams are useful for washout studies [55][56][57][58]. Therefore, our future work with the developed system will include a washout study with radioactive ion beams and entire-body scanning of animals.…”
Section: Discussionmentioning
confidence: 99%